Organizacje pozarządowe w systemie obronnym Polski .......... 217 - Adamkiewicz, Jakub; Trzcińska, Luiza (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
The chapter deals with the topic of pro-defense organizations in Poland. This issue is presented in the context of the perception of the rightful place of these entities in the defense system, which was checked based on their opinions and opinions of representatives of public institutions, in particular local government. The interview was preceded by an attempt to classify pro-defense organizations.